Branding First Class Dental Luxury Klinik Gigi OMDC, Analisis dengan Pendekatan Customer-Based Brand Equity (CBBE) - Fajaruddien Zakiany; Mirza Ronda (Prodi Sosiologi FISIP Universitas Teuku Umar, 2025)
This study aims to analyze the implementation of First Class Dental Luxury branding at OMDC Dental Clinic and to evaluate the alignment of this concept with patients’ perceptions using the Customer-Based Brand Equity (CBBE) framework. This research is important given the increasing competition in the dental healthcare industry, which requires brand differentiation not only in functional aspects but also in experiential and symbolic perceptions experienced by patients. A descriptive qualitative approach was employed, with data collected through in-depth interviews, observation, and documentation. Informants were selected using purposive sampling, involving internal stakeholders (management and dental professionals) and patients who had repeatedly utilized OMDC’s services, with the number of informants determined until theoretical saturation was achieved. Data analysis was conducted using Keller’s CBBE pyramid model, encompassing brand awareness, brand associations, perceived quality, and brand loyalty, and was integrated with indicators of healthcare service quality. The findings indicate that First Class Dental Luxury branding successfully differentiates OMDC Dental Clinic by delivering a service experience inspired by first-class airline services, characterized by an exclusive ambiance, personalized care, and professional interaction standards. Patients perceive a strong alignment between the brand image and the actual service experience, although greater consistency in implementation across all branches remains necessary. This study highlights the importance of integrating branding strategies with service quality to strengthen brand equity in the healthcare service sector.